As artes de governar no contexto da educação de surdos: estratégias de governamento da escola inclusiva - Cezimbra, Juliana (2014)
This study is part of the Research Field in Special Education of the Post Graduation Program in Education. It has as guiding issue to understand how the inclusive educational policies have been investing in conducting strategies of the deaf students‟ conduction in the inclusive school. Such enterprise of research follows a post structuralist approach by using the Foucauldian studies, more specifically the concept of governmentality as a central tool of the study. I approach specifically the school inclusion of a deaf student who attends the second year of Elementary School in the school Arroio Grande. I elected two groups of materials which I think were satisfactory to answer to the essential problematic of this study: the first group is composed of interviews conducted with the people involved with the inclusion process of the deaf student at school; the second is constituted by an analysis of the material Specialized Educational Assistance People with deafness. Throughout the thesis I present some discoveries of this research which are divided in three analytical categories: capture of bilingual education through the State, in this category I realize that AEE is constituted as a very strong discourse which refers to the strategies of effecting the inclusion, I would even say it appears in the discourses of MEC as assurance of school inclusion for students with disabilities. Another category named as: the visibility and consumption of Brazilian Sign Languages (Libras), I bring the discursive recurrences which indicated Libras as a tool of technical support to help in the deaf inclusion. For the third category, the normalization as a strategy of inclusion it was possible to notice how the strategies employed to effect the inclusion regulate, oversee and control, managing the risk, in a way that, in order to have the expected effect with the strategies, it is necessary that everyone can occupy the same space, considering that for the educational inclusion, the best environment is the school.